Ground state solution for a class of supercritical Hénon equation with variable exponent - Feng, Xiaojing (Topological Methods in Nonlinear Analysis, 2023)
This paper is concerned with the following supercritical Hénon equation with variable exponent cases -Δ u=|x|^α|u|^2^*_α-2+|x|^βu&in B, u=0 &on B, cases % where BR^N (N≥ 3) is the unit ball, α\!> \!0, 0\!< \!β\!< \!{(N\!+\!α)/2,N\!-\!2} and 2^*_α=(2N+2α)/(N-2). We obtain the existence of positive ground state solution by applying the mountain pass theorem, concentration-compactness principle and approximation techniques.